2010
DOI: 10.1111/j.1365-2591.2010.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of human pulps after professionally applied vital tooth bleaching

Abstract: Professionally applied vital tooth bleaching with a 38% H(2)O(2) gel with or without activation by a halogen light source did not cause damage to the pulp tissue of sound human premolar teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 31 publications
3
62
0
5
Order By: Relevance
“…The data obtained in this study corroborate those of previous investigations [6,20,21]. However, superficial zones of coronal pulp necrosis occurred in young human mandibular incisors even after a single clinical session of in-office bleaching [6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The data obtained in this study corroborate those of previous investigations [6,20,21]. However, superficial zones of coronal pulp necrosis occurred in young human mandibular incisors even after a single clinical session of in-office bleaching [6].…”
Section: Discussionsupporting
confidence: 90%
“…Based on the data obtained in this investigation as well as in previous in vivo studies [6,[20][21][22], new strategies for in-office bleaching therapy should be focused on preventing pulp damage and improving pulp cell regenerative potential. It was recently demonstrated that reducing the contact time of a 35%-HP gel (5-15 min) with enamel led to decreases in about 60% the transenamel and transdentinal diffusion of HP [26].…”
Section: Discussionmentioning
confidence: 78%
“…Since the tooth-bleaching process is mediated by ROS, which can diffuse through the enamel and dentin, reaching the pulp space [2], these aesthetic procedures can promote pulp alterations, such as mild inflammation or even partial necrosis [3][4][5]. Due to the deleterious effects caused by components of bleaching agents, which have been demonstrated in both in vitro [6][7][8][9][10] and in vivo studies [3,5,11], the evaluation of other bleaching techniques that can prevent or reduce pulp damage is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the deleterious effects caused by components of bleaching agents, which have been demonstrated in both in vitro [6][7][8][9][10] and in vivo studies [3,5,11], the evaluation of other bleaching techniques that can prevent or reduce pulp damage is needed. Thus, laser is promising coadjutant treatment that can be used in the photodynamic therapy [12,13], stimulate cell differentiation, reduction of inflammation, and tissue repair [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…7,8,9 While laboratory testing is a very useful method to study the diffusion of the components of bleaching gels, such H 2 O 2 , into dental pulp, 10,11 clinical trials can provide reliable and direct evidence to guide clinicians in their choice of materials for in-office and at-home bleaching. 12,13,14,15 Hence, randomized controlled trials (RCTs) are considered the standard research design for the evaluation of health interventions.…”
Section: Introductionmentioning
confidence: 99%